Nickel(II) and copper(II) complexes of Schiff base derived from isatin with 4-ethylaniline - Erçag, A; Turak, F; Özgür, MÜ; Bozdogan, A (ASIAN JOURNAL OF CHEMISTRY, 2006)
Ni(II) and Cu(II) complexes of Schiff base ligand derived from 4-ethylaniline with isatin (1H-indole-2,3-dione) were prepared. The chemical structures were confirmed by means of analytical and spectroscopic (IR, UV-Vis, FAAS, Mass) techniques as well as magnetic and thermal measurements. The complexes have 1 : 2 metal : ligand ratios and are paramagnetic. The IR spectra indicate that the ligand coordinates as bidentate through metal(II) ions via the carbonyl oxygen and the azomethine nitrogen. The complexes with the molecular formula [Cu(HL)(2)Cl-2]. [Ni(HL)(2)]Cl-2 are nonelectrolyte and I : 2 electrolyte, respectively. Solid state conductivities of synthesized compounds were measured using four-probe technique on a compressed pellet at room temperature. The ligand and Ni(II), Cu(II) complexes were studied potentiometrically in different aqua-organic solvent mixtures and temperatures. Protonation constants of the ligand and overall formation constants of the complexes were calculated from potentiometric data using the program TITFIT.
Keywords: isatin-anilines; Schiff bases; Ni(II) and Cu(II) complexes; potentiometric titration; MANNICH-BASES; CONDUCTIVITY; Chemistry